The Dynamics of Green Revolution Implementation in The Rice Farming Sector in Lamongan from 1970 to 1998 - Romadhona, Afrida Nurlaily; Pratama, Akhmad Ryan; Na'im, Mohamad; Swastika, Kayan; Jamil, Robit Nurul; Puja, Gusti Ngurah Ary Kesuma (JURNAL HISTORICA, 2024)
This research aims to analyze the reasons why Lamongan became the area for implementing the green revolution, along with the implementation of green revolution activities and their impact in Lamongan in 1970-1998. This research uses historical research methods with a city history approach using Pengembangan Ekonomi Lokal (PEL) based agriculture theory. Lamongan Regency, which is currently one of the largest rice producing areas on the island of Java, cannot be separated from the role of the Green Revolution program implemented by the New Order government in Lamongan. Seeing agricultural conditions in the 1960s where there was famine and floods which caused farmers to experience major crop failures, the Lamongan district government together with the New Order government with its agricultural revolution program made improvements starting from the water sector, extension to farmers, and so on which was oriented on increasing agricultural productivity and agricultural life, which is the livelihood of the majority of Lamongan residents. Having relatively stable agricultural land, production of agricultural products in Lamongan continues to increase from year to year. Its contribution reached 8.18% of East Java's total rice production. The impact of the Green Revolution in Lamongan in 1970-1980 can be seen in the economic growth of Lamongan Regency and the social life of farmers. Changes in Lamongan society can be seen in the level of education and educational facilities in Lamongan which continue to develop every year. The increase in the number of rice harvests from year to year during the green revolution, especially in 1984-1989, had an impact on increasing Lamongan regional income. Lamongan Regency's gross regional domestic product (GRDP) index increased. This increase in GRDP was triggered by the rapid increase in productivity in the agricultural sector, during the Green Revolution period 1970-1998.